Didactic possibilities of computer communications - the foundation of didactic model of training teachers in remote form - Vasilchenko L.V (Kharkov National Pedagogical University, 2010)
The didactic model of the remote form of raising the level of teacher's skill is considered. Directions of creation of single educational space of continuous education are rotined. The association of didactic possibilities of information telecommunication technologies is given by possibility to stimulate independent educational activity of teachers. The indicated system renders assistance to development of abilities in a short-story form to give information, create short information messages, assort necessary information on certain signs. All of it develops communicative capabilities which play an important role in development of the personal qualities of individual